P193 Assessement of cumulative bowel damage using Lemann index and MaRIA score in surgically naive patients with Crohn's disease. (27th May 2021) - Domislović, V; Hrabric Sonje, K; Brinar, M; Cukovic-Cavka, S; Turk, N; Grgic, D; Sjekavica, I; Krznaric, Z
Abstract: Background: The Lémann index (LI) is a unique tool that measures cumulative bowel damage in Crohn's disease (CD) using data on surgical procedures and severity and extent of bowel lesions. Magnetic resonance index of activity (MaRIA) is composed of features independently associated with endoscopic disease activity. Primary aim was to investigate differences in factors associated with elevated LI in total population and surgically naive patients. Secondary aim was to compare diagnostic accuracy of gMARIA and LI in determing active disease in surgically naive patients. Methods: In this cross-sectional study on 251 CD patients LI was calculated evaluating 20 small bowel, 7 large bowel and 3 upper GI segments. For each segment bowel resections, inflammatory, stricturing or penetrating lesions were taken into account. Global MaRIA (gMaRIA) index was calculated using following parameters on 6 bowel segments: bowel wall thickness, ulcers, edema and relative contrast enhancement. Longstanding disease was defined as ≥10 year disease duration. Disease activity was defined as combination of clinical and biochemical disease activity (CRP>5 or HBI≥5). Results: This study included 251 CD patients [age 35 (25–47), 55.3% males, disease duration 7 (2–15) years]. There were 103 (40%) surgically naïve and 112 (44.6%) patients with longstanding disease. In total population, higher LI values were observed in patients with longstanding disease (10.47 vs 5.41, p<0.001), patients treated with biological therapy (9.6 vs. 6.3, p=0.005) and with prior surgery (11.92 vs. 1.57, p<0.005). There was no difference in LI according to activity (7.53 vs. 7.66, p=0.911) and smoking status (6.9 vs. 7.3, p=0.336). In multivariate analysis adjusted for age, gender and BMI, independent predictors of elevated LI in total population was prior surgery (β=9.26, p<0.001) and disease duration (β=0.20, p<0.003). Independent predictors in surgically naive patients were current or ex smoking status (β=1.69, p<0.001) and gMARIA (β=0.10, p<0.001). Biological therapy, disease duration and clinical and biochemical disease activity were not significant predictors (p>0.05). Diagnostic accuracy of LI in surgically naive patients in defining active disease was lower [AUC 0.75 (95%CI 0.65–0.84)] compared to gMaRIA [AUC 0.82 (95%CI 0.73–0.89)]. Conclusion: Since surgical procedures contribute significantly to the LI, it is important to determine predictors of cumulative bowel damage in surgically naive patients. CD patients should be strongly advised to stop smoking and to regularly monitor disease activity using radiological methods. gMaRIA is superior to LI in detecting active disease in surgically naive patients.